2018
DOI: 10.1177/1687814017734133
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of microwave ablation on porous liver tissue

Abstract: The understanding of heat transport in biological tissues is important for enhanced insight on the physiological mechanisms and thermoregulatory mechanisms. This article presents a numerical simulation of microwave (MW) ablation using a single-slot MW antenna on two layers of porous liver tissue. The two layers are of tumor and normal tissue. A porous media approach is proposed for mathematical model of MW ablation. Three coupled models which include transient momentum equations and a transient energy equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Existing experimental studies available in literature have highlighted that the exposure of biological tissue to elevated temperatures (> 50 o C) during thermal ablative procedures can result in varying degree of mechanical deformation (including both expansion and contraction) within the tissue [24][25][26][27][28][29][30][31][32][33][34][35][36]. Several computational studies have also been reported to capture such mechanical deformations, but mainly limited to only thermal expansion [37][38][39][40][41][42][43]. Importantly, ignorance of the impact of tissue contraction/shrinkage during thermal ablative procedures has resulted in significant underestimation of the predicted ablation volume (see, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Existing experimental studies available in literature have highlighted that the exposure of biological tissue to elevated temperatures (> 50 o C) during thermal ablative procedures can result in varying degree of mechanical deformation (including both expansion and contraction) within the tissue [24][25][26][27][28][29][30][31][32][33][34][35][36]. Several computational studies have also been reported to capture such mechanical deformations, but mainly limited to only thermal expansion [37][38][39][40][41][42][43]. Importantly, ignorance of the impact of tissue contraction/shrinkage during thermal ablative procedures has resulted in significant underestimation of the predicted ablation volume (see, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…where ωb = 0.016 s -1 [12] is the baseline blood perfusion rate of the tissue. for hygienic and guidance purpose [37][38]. A continuous MWA procedure has been performed with the input MW power of 10-60 W for a duration of 10 minutes at the microwave antenna frequency of 2.45 GHz [38,44].…”
Section: Modeling Of Thermal Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Darcy law is derived for incompressible Newtonian fluid with neglecting the following factors: the divergence of the velocity, the inertial force, and the friction within the fluid and between the fluid and solid phases. Similar to other works in the literature 35,36 , the fluid flow in the tumor tissue with thermal ablation can be modelled using Darcy law.…”
Section: Methodsmentioning
confidence: 98%